The presence and abundance of harmful dinoflagellate algae related to water quality in Jakarta Bay, Indonesia - Annisa Khaira Nasution; Noverita Dian Takarina; Hikmah Thoha (Society for Indonesian Biodiversity, 2021)
Abstract. Takarina ND, Nasution AK, Thoha H. 2021. The presence and abundance of harmful dinoflagellate algae related to water quality in Jakarta Bay, Indonesia. Biodiversitas 22: 2909-2917. Dinoflagellate is a single-celled organism that commonly occurs in large numbers in marine environment. When environment changes, harmful dinoflagellate algae often emerge as a response to change in water quality. Jakarta Bay, Indonesia is the meeting point of 13 rivers that carry anthropogenic effluents, not only from agriculture and human settlements, but also industrial activities with some initial evidence showed the increasing growth of harmful algae population and decreasing water quality. This study aims to assess the correlations between dinoflagellate abundance and water quality parameters (i.e., dissolved oxygen, pH, salinity, temperature, and turbidity) in Jakarta Bay. Dinoflagellates were sampled in July 2020 at four river mouths, namely Ancol, Muara Baru, Muara Angke, and Muara Karang, each with three replications. Results showed that five dinoflagellates categorized as harmful were recorded. The following order of dinoflagellates based on abundance was Noctiluca > Ceratium > Gonyaulax > Gymnodinium > Dinophysis. Dinoflagellate abundance ranges were as low as 353,857 cells/m3 for Dinophysis and as high as 85,279,547 cells/m3 for Noctiluca. In terms of location, Muara Baru had the highest dinoflagellate abundance. There were correlations between dinoflagellate abundance with water quality. The dinoflagellate abundance was positively correlated with DO (Gymnodinium 0.5152; Dinophysis 0.5262; Gonyaulax 0.3701; Noctiluca 0.0429; Ceratium 0.4168) and temperature (Gymonodium 0.3894; Ceratium 0.3627; Gonyaulax 0.3428;Dinophysis 0.2536) but negatively correlated with pH (Ceratium-0.5558; Dinophysis-0.4868; Gymonodinium-0.4284; Noctiluca-0.4201; Gonyaulax-0.3881), turbidity (Dinophysis-0.2336; Gonyaulax-0.0105; Noctiluca-0.1164; Ceratium-0.0896), salinity (Gymnodinium-0.2176; Dinophysis-0.0888; Ceratium-0.0434).